Legal Protection For Brand Right Owner Famous For His Brand Immediate - Chris Anggi Natalia Berutu; Sheila Elfira; Monica Sheren Tambuwun; Ericson Sebastian Sitohang (Syiah Kuala Law Journal, 2021)
Brand equality can cause harm to brand owners. Therefore, the legal protection of trademarks is very important. In this study, the authors will analyze the Supreme Court Decision No. 7K/pdt.sus-HKI/2016 whose purpose is that the consequences of the law of imitation of famous brands can be known and know the legal protection for owners of well-known brands if their brands are imitated. This research is descriptive and classified as normative legal research and uses existing data. Based on research, the famous brand ST. REGIS belonging to the plaintiff entered the list of registrants in Indonesia first, therefore the defendant's mark REGIS@the Peak at Sudirman has been registered with unfavorable conditions. The defendant's mark is essentially the same as the plaintiff's mark for similar and dissimilar services, as a result, the defendant's mark must be removed from the general register of marks. According to the law, Sheraton Internasional as the owner of the famous ST.REGIS brand won against REGIS@ the Peak at Sudirman.